IT’S DANGEROUS TO LEARN ALONE – PLAY THIS: VIDEO GAMES IN HIGHER EDUCATION, PARTICULARLY IN THE COMPOSITION CLASSROOM - Sterrantino, Joy (Dialogue, 8(3), 2021)
When people think of educational games, they often just think of ones geared towards kids: these might include spelling and vocabulary games like Scribblenauts, creative games such as Minecraft , as well as historical games such as Carmen [Sandiego]’s Ancient Caper, but according to the Entertainment Software Association in 2019, 65% of adults play video games (almost half of which are female), the average gamer is 33 years old, and 63% of all gamers are playing with others at least one hour a week (“Essential Facts” 4, 5, 8). This means that the majority of the population plays video games of one type or another. Video games are part of most people’s discourse today, so it is odd that they are virtually ignored as a pedagogy once students enter middle or high school, and they certainly are not considered as a viable learning method in college. However, since games may be the key to how the majority of people of all ages learn best, it is a tool worth utilizing in higher education. I believe in particularly stressful classes, such as freshman composition, gamifying the classes can help reduce student stress and help achievement by couching complex and unfamiliar ideas in a fun and familiar structure. Thus, dialect is important because we often get caught up in “proper dialects,” academic language and in this case, traditional academic formats. And while these are important to learn, students can learn them better when working by adapting an already-effective language to new and often intimidating information. Gaming has been proven to be one of the most effective methods of motivation and feedback to exist which is exactly what students need. Keywords: video games, higher education, composition, writing, dialect, English, game, gaming, university, fun
Keywords: Type of access: Open Access